Menanamkan Nilai-Nilai Pancasila Dikalangan Generasi Muda Guna Menghadapi Ancaman Radikalisme di Era Glabalisasi - Zulfikar Putra Fikar; Suriaman (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this service is to provide an understanding of the importance of inculcating and practicing Pancasila values among the younger generation in facing the threat of radicalism in the era of globalization. This service activity is carried out in the form of an interactive dialogue where the resource person explains a certain theme then a discussion occurs from the presentation that has been delivered. The findings in the service carried out, that the precepts contained in Pancasila are only limited to memorization without concrete values. Through this service activity, students are expected to be able to understand well that Pancasila is a Weltanschauung (view of life), Philosofische Gronslag (the foundation of the nation's philosophy), and as the basis of the state and be able to internalize the values of Pancasila in family, community, nation and state life.